(3gOGjI GdCeI Edi CMcGe GdCFeIs - (3GdYGedj, GdMQ, eMeO Hf GdMSf Hf Ydj, J (B1104(3g`s ((3MSf Hf Ydj Hf MSjfs)
(3ChdgG (B:s
(3GYde Cfg EPG CWdb aj GdQhGjI bGd Udi Gddg Ydjg hSde aGdeQGO Hg GdfHj Udi Gddg Ydjg hBdg hEPG bjd CMOgeG aGdeQGO GdHGbQ hGdUGOb(B...s
(3BNQgG (B:s
(3jLH GdbUQ Ydi GdeSGaQ aj GdHMQ(B... (3hQhj Cf GdQVG Ydjg GdSdGe cGf jbUQ aj SaQg ef GdeOjfI Edi eQhs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3, U(B90s
(3EjVGM Gdecfhf(B: (3L(B2(3, U(B719s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis